Relevansi Agama Buddha Dengan Prinsip-Prinsip Sains Modern - Prita Puspita (Dhammavicaya : Jurnal Pengkajian Dhamma, 2020)
This study aims to find the relevance of Buddhism to the principles of Science. Discover the relationship between concepts in Buddhadharma with concepts that are the principles of science in various dimensions. Researchers conducted qualitativedescriptive-analysis research through a library approach. Researchers also take approaches that are based on paradigms and theoretical frameworks of Buddhist Studies and Philosophy of Science in seeing the relationship or relevance of Buddhadharma to science. The results of the study show the relevance or relationship between Buddhadharma and the principles of science as seen in the realm of scientific methodology and some issues investigated in various sciences. The results of research that show the relevance or compatibility of Buddhadharma with the principles of science can inspire a Buddhist in connection with his life and religious activities during the present era which is full of science and technology.